A FIELD STUDY ON ASSESSMENT OF THE FACTORS INCREASING PRODUCTIVITY OF SME’S: CASE OF ISTANBUL - Yılmaz GÖBENEZ (Sosyal Ekonomik Araştırmalar Dergisi, 2007)
The competitive environment which grows in size and intensity every day with globalization, and the rapid change in technology require SMEs to fully adapt to the present conditions. SMEs, which are among the most fundamental factors in our economy, and the productivity of SMEs, which is one of the most important targets for SMEs, are investigated in this study. In this respect, a questionnaire study was conducted through vis-à-vis interviews held at 108 SMEs in Istanbul, the province that shelters the highest number of SMEs in our country. In this analysis, a general evaluation was made on the SMEs in Turkey.